AB0854 Dysfunctional pain component in ankylosing spondylitis patients. (12th June 2018) - Filatova, E.; Erdes, S.
Abstract : Background: As a result of chronic inflammation, repetitive activation of primary afferent fibres changes the functional state and activity of Central nervous pathways. On this patients when describing their complaints use neuropathic pain descriptors include numbness, burning, tingling, increased pain response to a stimulus nabulivou etc. Objectives: The study of chronic pain syndrome in patients with ankylosing spondylitis (AS) to identify dysfunctional component of pain (DCP). Methods: Was studied 150 patients as 127 men and 23 women. The average age of 35, and 52±10, 55, mean disease duration of 7.19±of 6.31. All the patients were performed clinical and rheumatological examination (indices BASDAI, BASFI), the assessment of pain intensity on visual analogue scale (VAS), to identify DCP were investigated neurological status with the use of questionnaires neuropathic pain DN4 and PainDETECT, and identifying the emotional-affective disorders (HADS questionnaire). Results: 22 patients (14.7%) on the DN4 questionnaire revealed 4 or more points, but lesions of the somatosensory nervous system in these patients was not detected, hence 14, 7% of patients were identified DCP. When comparing patients with the presence of TCS group I (22 people) and no DCP group II (128) it has been found that statistically significantly in patients in group I had higher pain intensity on VAS (6, 09±185 vs 4, 55±2, 06, p=0.001, respectively); active disease BASDAI index (of 7.05±vs 1, 58 4, 87±2, 16, p=0.001, respectively); the expression of functional impairment index BASFI (6, 46±2, 24 vs 4, 05±2, 81, p=0.001); the indicators of the questionnaire HADS in group I, consistent with the presence of clinically significant anxiety and lack of it in group II (10, 09±2, 86 vs 6, 17±3, 35, p=0.0001). However, duration of disease distinguish authentic in the groups was not (9, 41±6, 89 6, 81 vs ±6, 13 p=0, 07). Correlation analysis revealed a significant relationship between DCP and the intensity of the pain in VAS back, as well as with the severity of anxiety, disease activity, functional disorders (p=0.05) Conclusions: The study identified 22 patients, the presence of neuropathic pain descriptors in combination with anxiety disorders, resulting in the conclusion that, along with nociceptive component of pain in 14.7% of cases detected by the DCT. So the pain of some AS patients should be considered as a multicomponent syndrome, providing a comprehensive approach with the use of antidepressants (TCA and SSRI's). Disclosure of Interest: None declared